Research on the Design and Implementation Strategy of Personalized Art Education Experience Based on AICG - Wang Jiaqi (SHS Web of Conferences)
This study explores the design and implementation strategies of personalized art education experience based on artificial intelligence generated content (AICG) technology. With the rapid development of AICG technology in the field of education, especially in art education, its potential impact on personalized educational experiences is increasingly receiving attention. The research objective is to explore how to use AICG technology to promote personalized design in art education, meet students’ different learning needs, and thus improve educational efficiency and quality. Firstly, the theoretical foundation section analyzes AICG technology and its application in education, combining personalized education theory and experiential design theory, emphasizing personalized learning paths, artistic creation, and experiential design in art education. The study also analyzed how AICG generates personalized content based on students’ interests and abilities, assists students in artistic creation, and enhances learning outcomes through multi-sensory and immersive experience design. Subsequently, the principles and strategies for personalized art education experience design were proposed, and the technical architecture and implementation path of the AICG platform were discussed, including data collection, model training and generation, content adaptation mechanism, etc. Through case analysis, this article evaluates the application of AICG based art education both domestically and internationally. Finally, the study summarized the application prospects of AICG in art education and proposed future research directions, including the integration of AICG with traditional education models and interdisciplinary art education applications.